Cellular and subcellular localization of protein I in the peripheral nervous system. - Fried, G (1982)
The cellular and subcellular distribution of protein I, a major brain phosphoprotein, has been studied in the peripheral nervous system. The levels of protein I in various peripheral nerves and innervated peripheral tissues were determined by radioimmunoassay and radioimmunolabeling of polyacrylamide gels. The results indicated tha protein I is present throughout the peripheral nervous system. Denervation studies of adrenal medulla and iris suggested that the protein I contained in peripheral tissues is localized to the neuronal elements innervating those tissues. Protein I was found to be enriched in neurotransmitter vesicle fractions of peripheral nervous tissue. Moreover, protein I appeared to be transported from cell bodies to axons terminals at least partly in association with neurotransmitter vesicles.